A vortical dawn flank boundary layer for near‐radial IMF: Wind observations on 24 October 2001. Issue 6 (19th June 2014) - Farrugia, C. J.; Gratton, F. T.; Gnavi, G.; Torbert, R. B.; Wilson, Lynn B.
Abstract We present an example of a boundary layer tailward of the dawn terminator which is entirely populated by rolled‐up flow vortices. Observations were made by Wind on 24 October 2001 as the spacecraft moved across the region at X ∼−13 RE. Interplanetary conditions were steady with a near‐radial interplanetary magnetic field (IMF). Approximately 15 vortices were observed over the 1.5 h duration of Wind's crossing, each lasting ∼5 min. The rolling up is inferred from the presence of a hot tenuous plasma being accelerated to speeds higher than in the adjoining magnetosheath, a circumstance which has been shown to be a reliable signature of this in single‐spacecraft observations. A blob of cold dense plasma was entrained in each vortex, at whose leading edge abrupt polarity changes of field and velocity components at current sheets were regularly observed. In the frame of the average boundary layer velocity, the dense blobs were moving predominantly sunward and their scale size along X was ∼7.4 RE. Inquiring into the generation mechanism of the vortices, we analyze the stability of the boundary layer to sheared flows using compressible magnetohydrodynamic Kelvin‐Helmholtz theory with continuous profiles for the physical quantities. We input parameters from (i) the exact theory of magnetosheath flow under aligned solar wind field and flow vectors near the terminator and (ii) the Wind data. It is shown that the configuration is indeed Kelvin‐Helmholtz (KH) unstable. This is the first reported example of KH‐unstable waves at the magnetopause under a radial IMF.